2019
DOI: 10.1016/j.jadohealth.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Dual Use Classification and Its Association With Nicotine Dependence and Quit Intentions

Abstract: Electronic cigarettes (e-cigarette) use is rapidly increasing in the U.S., especially among adolescents. A significant number of adolescents use both cigarettes and e-cigarettes, often referred to as dual use. We used a new classification of dual use, taking into account the frequency of use of both products. In addition, we examined the association between dual use with time to first cigarette after waking (a nicotine dependence measure) and quit intention. Methods: Data were drawn from the 2015e2018 National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 27 publications
(16 reference statements)
2
41
0
Order By: Relevance
“…Participants with high perceived risk could be concerned about the possibility of increased nicotine dependence or other risks associated with dual-use. 22,23 In addition, compared to those with low-risk perception, those with high-risk perception had higher odds of e-cigarette-only use relative to cigarette-only users. Our findings indicate that, relative to e-cigarette users, those with a high-risk perception of both products had lower odds of dual-use than those with a low-risk perception of both products.…”
Section: Discussionmentioning
confidence: 97%
“…Participants with high perceived risk could be concerned about the possibility of increased nicotine dependence or other risks associated with dual-use. 22,23 In addition, compared to those with low-risk perception, those with high-risk perception had higher odds of e-cigarette-only use relative to cigarette-only users. Our findings indicate that, relative to e-cigarette users, those with a high-risk perception of both products had lower odds of dual-use than those with a low-risk perception of both products.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, smoking intensity, a meaningful indication of one’s interest in quitting smoking, should be considered when examining use of novel tobacco products in association with facilitating smoking cessation. There have been numerous studies that evaluate the association between e-cigarette use and intention to quit cigarette smoking, some of which included an in-depth analysis in relation to cigarette-smoking frequency (e.g., daily versus non-daily smoking) [ 16 , 17 ] or daily cigarette consumption (e.g., number of cigarettes smoked per day) [ 18 , 19 ]. Meanwhile, other studies focused on the association between HTP use and intention to quit cigarette smoking [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…14,25 Evidence also shows that dual use of cigarettes and e-cigarettes is positively associated with illicit substance use, alcohol use, truancy, and poor academic performance and is negatively related to quit intention. 11,[18][19][20] The increase we observed in e-cigarette use among cigarette smokers is concerning and warrants further investigation. Over the 8 years analyzed, the mean age of first cigarette use increased significantly.…”
Section: Discussionmentioning
confidence: 81%
“…[15][16][17] Those who use combustible cigarettes and e-cigarettes concurrently could be at risk for increased substance abuse and other risky behavior. 11,[18][19][20] Analyzing youth smoking behavior over time provides additional insights to inform policy and prevention efforts. Jones et al 10 found that smoking intensity decreased among current cigarette-smoking youth, with heavy smokers decreasing from 18.0% to 7.8% and light smokers increasing from 67.2% in 1991 to 79.4% in 2009.…”
mentioning
confidence: 99%